Surveillance of Meeting the Youth Physical Activity Guideline: Impact of Including Vigorous-Intensity and Bone-Strengthening Activities. Issue 4 (2nd October 2022) - Hyde, Eric T.; Watson, Kathleen B.; Omura, John D.; Janz, Kathleen F.; Lee, Sarah M.; Fulton, Janet E.; Carlson, Susan A.
ABSTRACT: Purpose : The US youth physical activity guideline recommends participation in four types of physical activity: moderate-to-vigorous intensity aerobic (MVPA), vigorous-intensity aerobic (VPA), muscle-strengthening, and bone-strengthening physical activity. Current national prevalence estimates of meeting the youth physical activity guideline are typically based on measures of the MVPA and muscle-strengthening components. This study sought to examine differences in prevalence estimates using this current approach and then including measures of all four components. Methods : Data from US high school student respondents to the 2010 National Youth Physical Activity and Nutrition Survey were analyzed (n = 10, 596). Prevalence of students meeting the youth physical activity guideline were assessed and compared using 1) measures of MVPA and muscle-strengthening components only and 2) also including measures of the VPA and bone-strengthening components. Results : Overall, 15.2% students met the MVPA, 50.7% met the muscle-strengthening, 70.6% met the VPA, and 80.7% met the bone-strengthening components. In total, 12.1% (95% confidence interval: 10.9, 13.3) of students met both the MVPA and muscle-strengthening components, and 11.2% (95% confidence interval: 10.0, 12.4) met all four components. Conclusions : Incorporating additional measures of VPA and bone-strengthening activity into current surveillance systems may not meaningfully impact national estimates of meeting the youth physical activity guideline.